DINAMIKA PASAR UANG DAN PERAN SKEPTISISME PROFESIONAL AKUNTAN DALAM PENGAMBILAN KEPUTUSAN INVESTASI - Nizar Zulkarnain; Hendra Candra (POLITEKNIK LP3I JAKARTA, 2025)
The takeover of Silicon Valley Bank (SVB) by the Federal Deposit Insurance Corporation (FDIC) in March 2023, which occurred just a month after the bank was recognized as one of the top 20 banks in the United States, provides significant lessons regarding the uncertainty that can engulf even the most respected financial institutions. The study aims to identify various factors that influence investment decisions in the money market, focusing on the challenges faced by investors in the face of market uncertainty and limited information available. The approach method used is Qualitative Descriptive with data collection techniques using document studies, interviews and content analysis which are then analyzed using thematic analysis. The results of this study show that investment decision-making in the financial market is greatly influenced by various factors, both internal and external, including greed, overconfidence, media coverage, faith) and FOMO. Thus, it is necessary to be skeptical of professional accountants in determining investment decisions to reduce the risk of errors due to inaccurate or manipulative information.